2001
DOI: 10.12681/bgsg.17200
|View full text |Cite
|
Sign up to set email alerts
|

Migration and trapping of the Ionian series hydrocarbons (Epirus, NW Greece)

Abstract: Surface oil shows in the Ionian zone of NW Greece are mainly linked to the organic matter rich Lower Posidonia beds of Toarcian age and shale fragments within the Triassic breccias. The calcareous formations of the Ionian series are characterized by insignificant primary porosity-permeability. Only fractured carbonates might comprise potential reservoir rocks capped on top by the detrital series. Other prospective traps, with the evaporites playing the role of cap-rocks, are related to the degree of basement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 3 publications
1
13
0
4
Order By: Relevance
“…They have mainly been observed in faults, or in the contacts between the limestones and the overlying units (flysch, Burdigalian). Most exploration wells which have been drilled in the Ionian zone in the Epirus region have also provided some evidence for oil at depth (Karakitsios et al, 2001). Thus (Fig.…”
Section: Hydrocarbon Volumesmentioning
confidence: 93%
See 2 more Smart Citations
“…They have mainly been observed in faults, or in the contacts between the limestones and the overlying units (flysch, Burdigalian). Most exploration wells which have been drilled in the Ionian zone in the Epirus region have also provided some evidence for oil at depth (Karakitsios et al, 2001). Thus (Fig.…”
Section: Hydrocarbon Volumesmentioning
confidence: 93%
“…Hydrocarbon exploration activities in Western Greece have led in the past to the study of potential source rocks, mainly in the Ionian zone, while structural and stratigraphic trapping possibilities have also been discussed (IGRS-IFP, 1966;BP, 1971;Chiotis, 1983;Palakas et al, 1986;Jenkyns, 1988;Karakitsios, 1995;Roussos and Marnelis, 1995;Kamberis et al, 1996;Karakitsios and Rigakis, 1996;Rigakis andKarakitsios, 1998, Rigakis, 1999;Karakitsios et al, 2001;Zelilidis et al, 2003;Karakitsios, 2003;Rigakis et al, 2004). Data from these studies are reviewed in the following sections and is integrated with new data on potential source rocks in the Pre-Apulian zone.…”
Section: Oil Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic research since 1960 (IGRS-IFP, 1966;BP, 1971;Monopolis, 1977;Chiotis, 1983;C. Nikolaou, 1986, personal communication;Palakas et al, 1986;Karakitsios, 1992Karakitsios, , 1995Roussos and Marnelis, 1995;Karakitsios and Rigakis, 1996;Rigakis and Karakitsios, 1998;Karakitsios et al, 2001; Zelilidis et al, 2003;Rigakis et al, 2004;Karakitsios and Rigakis, 2007;Marnelis et al, 2007) has proven now that western Greece is characterized by rich source rocks of significant thickness, located in the Ionian and pre-Apulian (Paxos) zones. Limited early exploration focused on the abundant oil shows (Monopolis, 1977), and more recent exploration did not give encouraging results (Xenopoulos, 2000), although both Albania and Italy host substantial oil and gas fields (Mattavelli and Novelli, 1990;Van Greet et al, 2002;Mavromatidis et al, 2004;Roure et al, 2004;Graham Wall et al, 2006;Vilasi et al, 2009;Maravelis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…), making the area among the most promising, with respect to hydrocarbon prospectivity (Rigakis and Karakitsios, 1998;Zelilidis et al, 2003;Mavromatidis, 2009;Maravelis et al, 2012;Karakitsios, 2014). Research that conducted since 1960 demonstrated that western Greece hosts thick, organic-rich source rocks, located within both Ionian and pre-Apulian zones (IGRS-IFP, 1996;BP, 1971;Karakitsios, 1992;Karakitsios and Rigakis, 1996;Karakitsios et al, 2001;Zelilidis et al, 2003;Karakitsios and Rigakis, 2007;Maravelis et al, 2014). The nearby hydrocarbon discoveries and fields in Italy and Albania may be valid analogs since they share much of their geological history with western Greece.…”
Section: Introductionmentioning
confidence: 99%